Vimentin Inhibits Dengue Virus Type 2 Invasion of the Blood-Brain Barrier - Yu, Jianhai; Li, Xujuan; Zhou, Dongrui; Liu, Xuling; He, Xiaoen; Huang, Sheng-He; Wu, Qinghua; Zhu, Li; Yu, Linzhong; Yao, Jinxiu; Zhang, Bao; Zhao, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Dengue virus (DENV) causes dengue fever, which is prevalent in the tropical and subtropical regions and in recent years, has resulted in several major epidemics. Vimentin, a cytoskeletal component involved in DENV infection, is significantly reorganized during infection. However, the mechanism between DENV infection and Vimentin is still poorly understood. We generated vimentin knockout (Vim-KO) human brain microvascular endothelial cells (HBMECs) and a Vim-KO SV129 suckling mouse model, combined the dynamic vimentin changes observed in vitro and differences in disease course in vivo, to clarify the role of vimentin in DENV-2 infection. We found that the phosphorylation and solubility of vimentin changed dynamically during DENV-2 infection of HBMECs, suggesting regulation of vimentin by DENV-2 infection. The similar trends observed in phosphorylation and solubility of Vimentin showed that these characteristics are related. Compared with control cells, the DENV-2 viral load was significantly increased in Vim-KO HBMECs, and after DENV-2 infection, Vim-KO SV129 mice displayed more severe symptoms than normal SV129 mice, as well as higher viral loads in their serum and brain tissue, demonstrating that Vimentin can inhibit DENV-2 infection. Moreover, Vim-KO SV129 mice had more disordered cerebral cortical nerve cells, confirming that Vim-KO mice were more susceptible to DENV-2 infection, which causes severe brain damage. The findings of our study help clarify the mechanism by which vimentin inhibits DENV-2 infection and provides guidance for antiviral treatment strategy of DENV infection.